Catalytic cracking catalyst of rare earth metal modified ZMQ-1 molecular sieve

Through the combination of rare earth metal modified ZMQ-1 molecular sieve and double-layer mesoporous composite oxide, the problem of low cracking activity and selectivity of heavy hydrocarbons and susceptible to heavy metal contamination is solved, and the catalyst's cracking catalytic effect is achieved with high efficiency, stability and long-life cracking catalytic effect.

CN119897154APending Publication Date: 2025-04-29QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411836531.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the existing catalytic cracking technology, the catalyst has low cracking activity and selectivity for heavy hydrocarbons, is susceptible to heavy metal contamination and is inactive, and has poor structural stability in high temperature and high pressure environments.

Method used

Rare earth metal modified ZMQ-1 molecular sieve is used to optimize the distribution of acidity and metal activity centers of the molecular sieve through the loading of rare earth metals and synergistic metals, and a double-layer mesoporous composite oxide is constructed to enhance the mechanical strength and thermal stability of the catalyst.

Benefits of technology

It significantly improves the adsorption and cracking capacity of heavy hydrocarbons by the catalyst, enhances the selective generation of light hydrocarbons, extends the service life of the catalyst, reduces production costs and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897154A_ABST
    Figure CN119897154A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of petrochemical catalysis, and discloses a rare earth metal modified ZMQ-1 molecular sieve catalytic cracking catalyst, which comprises the following components by weight: 30%-50% of a rare earth metal modified ZMQ-1 molecular sieve, the total content of rare earth metal and synergistic metal being 5%-15% of the weight of the molecular sieve; 20%-40% of a double-layer mesoporous composite oxide; 15%-25% of a binder; the rare earth metal is optionally selected from one of Ce and La, and the synergistic metal is optionally selected from one of Ni and Pt. The ZMQ-1 molecular sieve is modified by rare earth metal, and synergistic metal is introduced, so that the distribution of acidity and metal active centers is optimized, the adsorption and cracking capability on heavy hydrocarbon is enhanced, the selectivity of light hydrocarbon is improved, and the petrochemical industry is assisted to obtain high-added-value raw materials; the double-layer mesoporous composite oxide is constructed, the inner layer promotes the oxidation reduction reaction, the outer layer keeps the structure stable, particles are prevented from being broken and pulverized, the reaction stability is maintained, the cost is reduced, and multiple remarkable advantages are brought to catalytic cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petrochemical catalysis, in particular to a catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve. Background Art

[0002] In the field of petrochemicals, catalytic cracking is a key process for the conversion of heavy oil to light oil, and traditionally relies on classic molecular sieve catalysts such as Y-type. However, as oil resources become heavier and inferior, it faces difficulties. On the one hand, traditional molecular sieves are mostly microporous structures, which are limited in the adsorption and conversion of large molecular heavy hydrocarbons, and have poor catalytic activity and selectivity. The yield of light hydrocarbon products is low, which makes it difficult to meet the market demand for raw materials such as ethylene and propylene, hindering the extension of the petrochemical industry chain. On the other hand, heavy oil contains heavy metal impurities such as nickel and vanadium, which are easily deposited on the surface of the catalyst to damage the active center, resulting in rapid deactivation of the catalyst, increasing replacement costs and reducing the operating efficiency of the device. Although new molecular sieves have been developed in recent years, such as new structure molecular sieves synthesized by introducing organic structure directing agents and heteroatom synthesis, there are defects such as easy collapse of the skeleton after removing the directing agent, complex synthesis conditions, and difficulty in large-scale stable production and poor repeatability.

[0003] Based on existing technologies, conventional molecular sieve catalysts cannot effectively cope with the complex composition and harsh working conditions of heavy oil. The microporous structure restricts the diffusion of reaction molecules, and the distribution of acidic and metal active centers is unreasonable, making it difficult to accurately catalyze the cracking of heavy hydrocarbons and to efficiently obtain light hydrocarbons. At the same time, heavy metal impurity contamination causes a sharp reduction in catalyst life, and frequent catalyst replacement seriously affects production continuity and economic benefits. Although the new molecular sieve has structural innovations, its stability and synthetic repeatability are insufficient, making it difficult to apply industrially. For the ZMQ-1 molecular sieve, although it has the advantage of a unique pore structure, the distribution of catalytic active sites is not optimized enough, and its ability to resist heavy metal pollution also needs to be strengthened, which limits its application efficiency in efficient catalytic cracking.

[0004] In summary, the field of petrochemical catalytic cracking urgently needs an innovative catalyst to break through the bottleneck of existing technologies. To this end, the present invention proposes a catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve, which solves the problems in the prior catalytic cracking technology of low catalyst activity and selectivity for heavy hydrocarbon cracking, susceptibility to deactivation due to heavy metal contamination, and poor structural stability under high temperature and high pressure environments.

[0006] To achieve the above object, the present invention is implemented by the following technical scheme: A catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve, comprising the following components by weight percentage:

[0007] Rare earth metal modified ZMQ-1 molecular sieve 30%-50%, wherein the total content of rare earth metal and synergistic metal is 5%-15% of the molecular sieve weight;

[0008] Double-layer mesoporous composite oxide 20%-40%;

[0009] Binder 15%-25%;

[0010] Enhancer 5%-10%.

[0011] Preferably, the rare earth metal is one of Ce or La, and the synergistic metal is one of Ni and Pt.

[0012] Preferably, the loading distribution uniformity of the rare earth metal and the synergistic metal on the rare earth metal-modified ZMQ-1 molecular sieve is not less than 80%.

[0013] Preferably, the double-layer mesoporous composite oxide comprises an inner layer of CeO2-La2O3 and an outer layer of TiO2-SiO2.

[0014] Preferably, the specific surface area of ​​the double-layer mesoporous composite oxide is 200-500m 2 / g, pore volume is 0.3-0.8cm 3 / g.

[0015] Preferably, the binder comprises gamma alumina and kaolin in a mass ratio of 1:1, and the reinforcing agent is nano-silicon dioxide.

[0016] Preferably, the rare earth metal modified ZMQ-1 molecular sieve is prepared by the following steps:

[0017] S1.1, calcining ZMQ-1 molecular sieve at a temperature of 550°C-600°C for 4-6h;

[0018] S1.2, impregnate the calcined molecular sieve with a rare earth metal salt solution with a concentration of 0.1 mol / L, a solid-liquid ratio of 1:10, and an impregnation time of 2-6 hours;

[0019] S1.3, drying the impregnated molecular sieve at a temperature of 80°C-120°C for 10-12h;

[0020] S1.4, repeat the above impregnation and drying steps, using a synergistic metal salt solution with a concentration of 0.05 mol / L;

[0021] S1.5, calcining the molecular sieve at a temperature of 550°C to 600°C for 4-6 hours;

[0022] S1.6. Carry out reduction treatment in a hydrogen or nitrogen reducing atmosphere at 400°C-450°C for 3-5 hours.

[0023] Preferably, the double-layer mesoporous composite oxide is prepared by the following steps:

[0024] S2.1, prepare the inner layer CeO2-La2O3, mix Ce(NO3)3·6H2O and La(NO3)3·6H2O in a molar ratio of 1:1, dissolve in deionized water, add ammonia water to adjust the pH to 9, wash and dry the precipitate after reaction at a temperature of 100℃-150℃ for 10-12h;

[0025] S2.2, followed by calcination at a temperature of 500°C-700°C for 3-6h;

[0026] S2.3, suspend the inner layer particles in TiO2-SiO2 sol, stir to coat, dry and then calcine at a temperature of 450℃-600℃ for 4-8h to form an outer layer.

[0027] Preferably, the molar ratio of Ti or Si in the TiO2-SiO2 sol is 2:1 to 5:1.

[0028] Preferably, the catalyst is formed by the following process:

[0029] The rare earth metal modified ZMQ-1 molecular sieve, the double-layer mesoporous composite oxide, the binder and the reinforcing agent are mixed in a ratio of 4:2:2:1 respectively according to weight percentage;

[0030] Add deionized water, control the moisture content to 20%-25%, stir evenly for 1-3 hours;

[0031] Pellets with a diameter of 2-4 mm are prepared by extrusion molding equipment;

[0032] The particles are calcined in an air atmosphere at a temperature of 550°C-600°C for 4-6 hours;

[0033] The secondary calcination is carried out in an inert atmosphere at a temperature of 750°C-800°C for 6-8h.

[0034] The present invention provides a catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve, which has the following beneficial effects:

[0035] 1. The present invention modifies the ZMQ-1 molecular sieve by rare earth metals and introduces synergistic metals, which can effectively adjust the acidity of the molecular sieve and the distribution of metal active centers, so that the catalyst's adsorption and cracking capabilities for heavy hydrocarbon molecules in catalytic cracking reactions are significantly enhanced, thereby improving the selective generation of light hydrocarbons, providing strong support for obtaining more high-value-added basic chemical raw materials in the petrochemical industry, and is conducive to improving the economic benefits of related industrial chains.

[0036] 2. The present invention constructs a double-layer mesoporous composite oxide. The inner layer CeO2-La2O3 provides good redox properties, which can promote certain redox reactions and help improve the catalyst's conversion efficiency of specific impurities or reactants in the raw materials; the outer layer CeO2-La2O3 enhances the mechanical strength and thermal stability of the catalyst. In the high temperature and high pressure environment of catalytic cracking, this structure can effectively prevent the catalyst particles from breaking and pulverizing, maintain the physical structural integrity of the catalyst, ensure the continuous and stable progress of the catalytic reaction, reduce the performance degradation and replacement frequency caused by catalyst structural damage, reduce production costs and improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The flowchart of the preparation steps of the rare earth metal modified ZMQ-1 molecular sieve of the present invention;

[0038] Figure 2 The figure is a flow chart of the preparation steps of the double-layer mesoporous composite oxide of the present invention;

[0039] Figure 3 The present invention is a process flow chart for preparing the catalyst. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Please refer to the attached Figure 1 -Attached Figure 3 The embodiment of the present invention provides a catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve, which comprises the following components by weight percentage:

[0042] Rare earth metal modified ZMQ-1 molecular sieve 30%-50%, wherein the total content of rare earth metal and synergistic metal is 5%-15% of the molecular sieve weight; double-layer mesoporous composite oxide 20%-40%; binder 15%-25%; reinforcing agent 5%-10%.

[0043] Specifically, ZMQ-1 molecular sieve becomes the core catalytic component after being modified by rare earth metals. The appropriate amount of rare earth metals can effectively adjust the distribution of acid sites of molecular sieves. By interacting with the oxygen atoms of the skeleton, it changes the local electron cloud environment, making the strength and distribution of the acid center more consistent with the cracking requirements of heavy hydrocarbon molecules, and significantly improving the catalytic activity. Synergistic metals further cooperate with rare earth metals to optimize the function of metal active centers. The synergistic effect of the two precisely guides the reaction path, improves the selective generation of light hydrocarbons, and meets the petrochemical industry's demand for high value-added basic chemical raw materials.

[0044] The redox performance of the inner layer of the double-layer mesoporous composite oxide, CeO2-La2O3, is extremely critical for the conversion of impurities such as sulfur and nitrogen in catalytic cracking raw materials. It can effectively improve the catalyst's conversion efficiency for these specific impurities or reactants and improve product quality. The outer layer is also CeO2-La2O3, and its main function is to enhance the overall mechanical strength and thermal stability of the catalyst. In the high-temperature and high-pressure catalytic cracking environment, it effectively prevents the catalyst particles from breaking and pulverizing, maintains the integrity of the physical structure, ensures that the catalytic reaction continues to proceed stably, and reduces performance degradation and replacement frequency caused by structural damage, thereby reducing production costs and improving production efficiency.

[0045] The rare earth metal may be selected from Ce or La, and the synergistic metal may be selected from Ni and Pt.

[0046] The loading distribution uniformity of the rare earth metal and the synergistic metal on the rare earth metal modified ZMQ-1 molecular sieve is not less than 80%.

[0047] Specifically, Ce or La is selected as a rare earth metal because they have unique electronic structures and chemical properties. Ce and La can interact effectively with the framework of the ZMQ-1 molecular sieve, thereby changing the distribution of acid sites of the molecular sieve. For example, the Ce element can be converted between different oxidation states (Ce 3+ and Ce 4+ ), this redox property can adjust the reaction atmosphere during the catalytic cracking reaction and promote the activation and cracking of heavy hydrocarbon molecules. La element has a larger ionic radius, which can produce a certain steric hindrance effect in the framework of the molecular sieve, change the pore environment of the molecular sieve, and facilitate the adsorption and diffusion of the reactant molecules.

[0048] One of Ni and Pt is selected as the synergistic metal because they have excellent hydrogenation / dehydrogenation performance in catalytic reactions. In the catalytic cracking process, Ni and Pt can form a synergistic effect with rare earth metals to promote the carbon-carbon bond breaking and hydrogen transfer reaction of heavy hydrocarbon molecules. For example, Pt has high hydrogen adsorption and dissociation capabilities and can provide active hydrogen atoms during the reaction process. These hydrogen atoms can stabilize the reaction intermediates and prevent excessive cracking and the formation of carbon deposits. Ni performs well in hydrogenation reactions, can increase the saturation of the product, and help generate high-quality light hydrocarbon products.

[0049] It is crucial that the loading distribution uniformity of rare earth metals and synergistic metals on the molecular sieve is not less than 80%. Uniform loading distribution can ensure that each active center can effectively participate in the catalytic reaction and avoid the situation where the local activity is too high or too low. If the loading is uneven, in areas where the active centers are densely distributed, it may cause excessive reactions, produce too many by-products or accelerate the formation of carbon deposits; while in areas where the active centers are sparse, heavy hydrocarbon molecules may not be fully cracked, reducing the overall catalytic efficiency of the catalyst.

[0050] Highly uniform load distribution (not less than 80%) can maximize the synergistic catalytic effect of rare earth metals and synergistic metals with ZMQ-1 molecular sieve. This enables the catalyst to more stably and efficiently adsorb and crack heavy hydrocarbon molecules throughout the reaction process, accurately control the reaction path, improve the selective generation of light hydrocarbons, and help maintain the activity and stability of the catalyst, extending its service life, thereby improving the economy and efficiency of the entire catalytic cracking process.

[0051] The double-layer mesoporous composite oxide includes an inner layer of CeO2-La2O3 and an outer layer of TiO2-SiO2.

[0052] The specific surface area of ​​the double-layer mesoporous composite oxide is 200-500m2 / g, and the pore volume is 0.3-0.8cm3 / g.

[0053] Please refer to the attached Figure 1 , rare earth metal modified ZMQ-1 molecular sieve is prepared by the following steps:

[0054] S1.1, calcining ZMQ-1 molecular sieve at a temperature of 550°C-600°C for 4-6h;

[0055] S1.2, impregnate the calcined molecular sieve with a rare earth metal salt solution with a concentration of 0.1 mol / L, a solid-liquid ratio of 1:10, and an impregnation time of 2-6 hours;

[0056] S1.3, drying the impregnated molecular sieve at a temperature of 80°C-120°C for 10-12h;

[0057] S1.4, repeat the above impregnation and drying steps, using a synergistic metal salt solution with a concentration of 0.05 mol / L;

[0058] S1.5, calcining the molecular sieve at a temperature of 550°C to 600°C for 4-6 hours;

[0059] S1.6. Carry out reduction treatment in a hydrogen or nitrogen reducing atmosphere at 400°C-450°C for 3-5 hours.

[0060] Please refer to the attached Figure 2 , the double-layer mesoporous composite oxide is prepared by the following steps:

[0061] S2.1, prepare the inner layer CeO2-La2O3, mix Ce(NO3)3·6H2O and La(NO3)3·6H2O in a molar ratio of 1:1, dissolve in deionized water, add ammonia water to adjust the pH to 9, wash and dry the precipitate after reaction at a temperature of 100℃-150℃ for 10-12h;

[0062] S2.2, followed by calcination at a temperature of 500°C-700°C for 3-6h;

[0063] S2.3, suspend the inner layer particles in TiO2-SiO2 sol, stir to coat, dry and then calcine at a temperature of 450℃-600℃ for 4-8h to form an outer layer.

[0064] The molar ratio of Ti or Si in the TiO2-SiO2 sol is 2:1 to 5:1.

[0065] Please refer to the attached Figure 3 , the catalyst is formed by the following process:

[0066] The rare earth metal modified ZMQ-1 molecular sieve, the double-layer mesoporous composite oxide, the binder and the reinforcing agent are mixed in a ratio of 4:2:2:1 respectively according to weight percentage;

[0067] Add deionized water, control the moisture content to 20%-25%, stir evenly for 1-3 hours;

[0068] Pellets with a diameter of 2-4 mm are prepared by extrusion molding equipment;

[0069] The particles are calcined in an air atmosphere at a temperature of 550°C-600°C for 4-6 hours;

[0070] The secondary calcination is carried out in an inert atmosphere at a temperature of 750°C-800°C for 6-8h.

[0071] Embodiment 1:

[0072] Preparation of rare earth metal modified ZMQ-1 molecular sieve:

[0073] La was selected as the rare earth metal, and the ZMQ-1 molecular sieve was calcined at 550°C for 6h.

[0074] It was impregnated with 0.1 mol / L lanthanum nitrate solution, solid-liquid ratio 1:10, impregnation time 6 hours, and then dried at 80°C for 12 hours.

[0075] The impregnation and drying steps were then repeated using a nickel nitrate solution with a concentration of 0.05 mol / L.

[0076] Finally, it was calcined at 550°C for 6 h and reduced at 400°C in a hydrogen reducing atmosphere for 5 h.

[0077] Preparation of double-layer mesoporous composite oxides:

[0078] To prepare the inner layer of CeO2-La2O3, Ce(NO3)3·6H2O and La(NO3)3·6H2O were mixed in a 1:1 molar ratio, dissolved in deionized water, and adjusted to pH 9 by adding ammonia water. After precipitating and washing, the mixture was dried at 100°C for 12h and calcined at 500°C for 6h.

[0079] A TiO2-SiO2 sol with a Ti / Si molar ratio of 2:1 was prepared, and the inner layer particles were suspended therein, stirred for coating, and then dried and calcined at 450°C for 8 h to form an outer layer.

[0080] Catalyst molding:

[0081] Rare earth metal modified ZMQ-1 molecular sieve, double-layer mesoporous composite oxide, binder, wherein the mass ratio of gamma alumina and kaolin is 1:1, and reinforcing agent (nano-silica) are mixed in a weight ratio of 4:2:2:1.

[0082] Deionized water was added to control the moisture content to 20% and stirred for 3 h.

[0083] Pellets with a diameter of 2 mm were prepared by extrusion molding, calcined at 550°C in air atmosphere for 6 h, and re-calcined at 750°C in nitrogen inert atmosphere for 8 h.

[0084] Summary: In this example, La is used as a rare earth metal to modify the ZMQ-1 molecular sieve, the molecular sieve is calcined at a lower temperature of 550°C and a longer time of 6h, the metal salt solution is treated with a specific concentration and immersion time, and then calcined again at 550°C and reduced with hydrogen at 400°C. In the preparation of the double-layer mesoporous composite oxide, the inner layer CeO2-La2O3 is synthesized according to the conventional method and calcined at 500°C, and the outer layer is calcined at 450°C after coating with a sol with a Ti / Si molar ratio of 2:1. When the catalyst is formed, the components are mixed in proportion, and 2mm particles are made after stirring for 3h under a control of 20% moisture, first calcined at 550°C in air for 6h, and then calcined again at 750°C in nitrogen for 8h. This example determines the basic preparation process and parameter combination, provides a basic reference for subsequent examples, and preliminarily demonstrates the operability and performance basis of the catalyst system under standard process conditions.

[0085] Embodiment 2:

[0086] Preparation of rare earth metal modified ZMQ-1 molecular sieve:

[0087] Ce was selected as the rare earth metal, and the ZMQ-1 molecular sieve was calcined at 600°C for 4h.

[0088] It was impregnated with a 0.1 mol / L cerium nitrate solution with a solid-liquid ratio of 1:10 for 2 hours, and then dried at 120°C for 10 hours.

[0089] The immersion and drying steps were then repeated using a 0.05 mol / L chloroplatinic acid solution.

[0090] Finally, it was calcined at 600 °C for 4 h and reduced at 450 °C in a nitrogen reducing atmosphere for 3 h.

[0091] Preparation of double-layer mesoporous composite oxides:

[0092] To prepare the inner layer of CeO2-La2O3, Ce(NO3)3·6H2O and La(NO3)3·6H2O were mixed in a 1:1 molar ratio, dissolved in deionized water, and ammonia water was added to adjust the pH to 9. After the precipitate was washed, it was dried at 150°C for 10h and calcined at 700°C for 3h.

[0093] A TiO2-SiO2 sol (Ti / Si molar ratio of 5:1) was prepared, and the inner layer particles were suspended therein, stirred for coating, and then dried and calcined at 600°C for 4 h to form an outer layer.

[0094] Catalyst molding:

[0095] Rare earth metal-modified ZMQ-1 molecular sieve, double-layer mesoporous composite oxide, binder (gamma alumina and kaolin in a mass ratio of 1:1) and reinforcing agent (nano-silica) are mixed in a weight ratio of 4:2:2:1.

[0096] Deionized water was added to control the moisture content to 25% and stirred for 1 h.

[0097] Pellets with a diameter of 4 mm were prepared by extrusion molding, calcined at 600°C in air atmosphere for 4 h, and re-calcined at 800°C in argon inert atmosphere for 6 h.

[0098] Summary: This example uses Ce as a rare earth metal, calcines the ZMQ-1 molecular sieve at a high temperature of 600°C for 4h, adjusts the parameters such as the impregnation time to 2h and the drying temperature to 120°C for metal loading, and then treats it with a chloroplatinic acid solution and calcines it at 600°C and reduces it with nitrogen at 450°C. In the preparation of double-layer mesoporous composite oxides, the inner layer calcination temperature is increased to 700°C, and the outer layer is calcined at 600°C after coating with a sol with a Ti / Si molar ratio of 5:1. During molding, 25% of the water is controlled and stirred for 1h to form 4mm particles, which are calcined in air at 600°C for 4h and then calcined again at 800°C for argon for 6h. This example expands the scope of process parameter exploration by changing the type of rare earth metal and the values ​​of key parameters in each step, and compares and studies the potential effects of different process conditions on the structure and performance of the catalyst, which helps to deeply understand the role of each parameter in catalyst preparation.

[0099] Embodiment three:

[0100] Preparation of rare earth metal modified ZMQ-1 molecular sieve:

[0101] A mixture of La and Ce (molar ratio 1:1) was selected as rare earth metals, and the ZMQ-1 molecular sieve was calcined at 580°C for 5h.

[0102] The sample was impregnated with a mixed solution of lanthanum nitrate and cerium nitrate at a concentration of 0.1 mol / L, a solid-liquid ratio of 1:10, an immersion time of 4 h, and then dried at 100°C for 11 h.

[0103] Then, the impregnation and drying steps were repeated using a mixed solution of nickel nitrate and chloroplatinic acid (molar ratio 1:1) with a concentration of 0.05 mol / L.

[0104] Finally, it was calcined at 580°C for 5h and reduced at 425°C in a reducing atmosphere of a mixture of hydrogen and nitrogen (volume ratio 1:1) for 4h.

[0105] Preparation of double-layer mesoporous composite oxides:

[0106] To prepare the inner layer of CeO2-La2O3, Ce(NO3)3·6H2O and La(NO3)3·6H2O were mixed in a 1:1 molar ratio, dissolved in deionized water, and adjusted to pH 9 by adding ammonia water. After precipitating and washing, it was dried at 125°C for 11h and calcined at 600°C for 4.5h.

[0107] A TiO2-SiO2 sol (Ti / Si molar ratio of 3:1) was prepared, and the inner layer particles were suspended therein, stirred for coating, and then dried and calcined at 525°C for 6 h to form an outer layer.

[0108] Catalyst molding:

[0109] Rare earth metal-modified ZMQ-1 molecular sieve, double-layer mesoporous composite oxide, binder (gamma alumina and kaolin in a mass ratio of 1:1) and reinforcing agent (nano-silica) are mixed in a weight ratio of 4:2:2:1.

[0110] Deionized water was added to control the moisture content to 22.5% and stirred for 2 h.

[0111] Pellets with a diameter of 3 mm were prepared by extrusion molding, calcined at 580°C in air atmosphere for 5 h, and re-calcined at 775°C in nitrogen inert atmosphere for 7 h.

[0112] Summary: Example 3: La and Ce were mixed in a 1:1 molar ratio as rare earth metals to modify the ZMQ-1 molecular sieve, calcined at 580°C for 5h, impregnated with a mixed metal salt solution and dried at 100°C for 11h, then treated with a mixed synergistic metal solution, calcined at 580°C and reduced in a mixed atmosphere at 425°C. When preparing a double-layer mesoporous composite oxide, the inner layer drying temperature was optimized to be 125°C and the calcination temperature was 600°C. The outer layer was calcined at 525°C after coating with a sol with a Ti / Si molar ratio of 3:1. Catalyst molding: Mix the components in proportion, control the moisture content to 22.5%, stir for 2h to make 3mm particles, calcine at 580°C in air for 5h, and then calcine again at 775°C in nitrogen for 7h. This embodiment innovatively introduces mixed rare earth metals and mixed synergistic metals, and at the same time fine-tunes the preparation and molding parameters of each component, aiming to comprehensively optimize the microstructure and macroscopic properties of the catalyst by combining multiple factors, and provides a more comprehensive and in-depth technical solution and practical experience for the development of high-performance, multifunctional catalytic cracking catalysts.

[0113] Summary: Through these three examples, from the basic single rare earth metal and single synergistic metal, conventional process parameter settings, to changing the metal type and parameter value range exploration, and then to the use of mixed metals for preparation, the preparation process of the catalytic cracking catalyst of the rare earth metal modified ZMQ-1 molecular sieve and its influence on the catalyst performance are gradually and deeply studied. Each example provides valuable data and ideas for further optimizing the composition and preparation process of the catalyst on the premise of meeting the overall technical solution, which will help to develop catalytic cracking catalysts with better performance in subsequent research to meet the catalytic cracking needs in different industrial scenarios.

[0114] The performance test experiments of the catalysts prepared in the above three embodiments:

[0115] 1. Purpose of the experiment

[0116] The activity, selectivity, stability and anti-carbon deposition performance of the catalysts prepared in the three examples in catalytic cracking reactions were systematically evaluated, and the influence mechanism of different preparation process parameters on catalyst performance was deeply explored, providing comprehensive and accurate data support and theoretical basis for further optimization and improvement of the catalyst.

[0117] 2. Experimental Materials and Instruments

[0118] Experimental Materials:

[0119] The catalyst samples prepared in Examples 1, 2 and 3 were ground and sieved before the experiment, and particles of 20-40 mesh were selected for use.

[0120] The simulated heavy oil feedstock is a mixture of various alkanes, aromatics, and sulfur- and nitrogen-containing compounds. It has typical heavy oil characteristics and its metal (such as nickel, vanadium, etc.) content is accurately determined.

[0121] High-purity nitrogen (purity ≥ 99.999%) and hydrogen (purity ≥ 99.99%) are used as purge gas, carrier gas and reducing gas of the reaction system.

[0122] Experimental instruments: Continuous flow fixed bed reaction device, including reactor (made of stainless steel, inner diameter 10mm, length 500mm), heating furnace (temperature can be accurately controlled to ±1℃), feed pump (flow accuracy ±0.1%), back pressure valve (pressure control accuracy ±0.05MPa) and other components. Gas chromatograph (Agilent7890A, equipped with hydrogen flame ionization detector FID and thermal conductivity detector TCD), used to analyze the composition of light hydrocarbons in gas products and liquid products. Element analyzer (such as VarioELI II), used to determine the content of carbon, hydrogen, nitrogen, sulfur and other elements in liquid products. Thermogravimetric analyzer (TAQ500), used to analyze the amount of carbon deposits and carbon deposit properties on the catalyst after the reaction. Electronic balance (accuracy 0.0001g), used to accurately weigh the catalyst loading, raw material feed and product collection.

[0123] 3. Experimental steps

[0124] In the glove box, carefully load the treated catalyst into the constant temperature section of the reactor, with a loading height of 300mm. Use the segmented loading method and slightly vibrate the reactor to make the catalyst bed uniform and tight. Fill the upper and lower ends with 50mm high inert quartz sand to prevent the channeling of raw materials and products. After the loading is completed, use an electronic balance to accurately weigh the mass of the loaded catalyst. Connect the various components of the reaction device and check the air tightness of each connecting pipeline. Use nitrogen to purge the entire reaction system. First, purge at a flow rate of 100mL / min for 1 hour to remove air and impurities in the system, and then reduce the nitrogen flow rate to 20mL / min, maintain the system positive pressure, and turn on the heating furnace at the same time to preheat the reactor to the reaction temperature (450℃ for the primary reactor and 600℃ for the secondary reactor). Turn on the feed pump, flush and calibrate the feed pipeline with a solvent (such as n-heptane) to ensure the accuracy of the feed amount. Set the back pressure valve pressure to 0.1MPa (primary reactor outlet) and 0.2MPa (secondary reactor outlet).

[0125] Catalyst pre-reduction (if necessary): For catalysts containing reducible metals (such as the catalyst treated in a hydrogen / N2 reducing atmosphere in Example 1), a pre-reduction operation is required before the reaction. Raise the reactor temperature to the reduction temperature (such as 400°C), switch the gas to a hydrogen / nitrogen mixed gas (the volume ratio is set according to the catalyst requirements, such as 1:9), pass through the catalyst bed at a flow rate of 50mL / min, and the reduction time is 4 hours. After the reduction is completed, switch back to nitrogen purging, and start feeding the raw materials after the temperature drops to the reaction temperature.

[0126] Reaction process: After the simulated heavy oil feedstock is preheated to 300°C, it is transported to the top of the primary reactor by the feed pump at a set flow rate (the feed rate of the primary reactor is 10mL / h, and the feed rate of the secondary reactor is calculated according to the catalyst / feedstock ratio) for reaction. After the reaction product flows out from the bottom of the primary reactor, it is heated to the inlet temperature of the secondary reactor through the heating pipeline and enters the secondary reactor to continue the reaction.

[0127] During the reaction, liquid products and gaseous products were collected from the gas-liquid separator at the reactor outlet every hour. The liquid products were collected in pre-weighed sample bottles, and the gaseous products were switched through a six-way valve into a gas chromatograph for online analysis at an interval of 30 minutes.

[0128] Product analysis; Gas product analysis: Use gas chromatograph (FID to detect hydrocarbons, TCD to detect hydrogen, nitrogen and other permanent gases) to analyze the content of each component in the gas product (including light hydrocarbons such as ethylene, propylene, methane, ethane, propane, as well as hydrogen, nitrogen, carbon monoxide, carbon dioxide, etc.), use standard gas mixture to calibrate the chromatographic column and establish the quantitative analysis method, and use the external standard method to calculate the volume fraction of each component.

[0129] Liquid product analysis: Weigh the collected liquid product and calculate the yield of the liquid product. Then use a distillation device to separate the liquid product into a gasoline fraction (initial boiling point -200°C), a diesel fraction (200°C-350°C) and a heavy fraction (>350°C), record the volume and mass of each fraction, and calculate its yield.

[0130] A certain amount of gasoline fraction and diesel fraction was taken and a detailed hydrocarbon composition analysis was performed using a gas chromatography-mass spectrometer (GC-MS) to determine the distribution of various hydrocarbons such as alkanes, cycloalkanes, and aromatics.

[0131] An elemental analyzer is used to determine the contents of carbon, hydrogen, nitrogen and sulfur in the liquid product, and parameters such as the hydrogen-to-carbon ratio, nitrogen content and sulfur content are calculated to evaluate the catalyst's ability to remove heteroatoms in the raw material.

[0132] Catalyst carbon deposition analysis: After the reaction is completed, the catalyst in the reactor is cooled to room temperature under nitrogen protection, and a portion of the catalyst sample (about 100 mg) is taken out for carbon deposition analysis using a thermogravimetric analyzer. The sample is heated from room temperature to 800°C at a heating rate of 10°C / min, and the weight loss of the catalyst is measured in a nitrogen atmosphere. The amount of carbon deposition on the catalyst is calculated based on the weight loss curve, and the type of carbon deposition (such as soft carbon deposition and hard carbon deposition) is determined by analyzing the characteristic peaks of thermal decomposition of carbon deposition.

[0133] IV. Experimental Design

[0134] A completely randomized experimental design was adopted, and the catalysts prepared in the three embodiments were used as three treatment groups, and each treatment group was subjected to three repeated experiments. The experiments were conducted under the same reaction conditions, raw material properties and analytical methods to eliminate the influence of systematic errors on the experimental results and ensure the reliability and comparability of the experimental data.

[0135] 5. Experimental results data table

[0136] Table 1: Product yield data

[0137]

[0138]

[0139] Table 2: Product quality data

[0140] catalyst Hydrogen to Carbon Ratio Nitrogen content (ppm) Sulfur content (ppm) Example 1 (repeat 1) 1.65 600 1500 Example 1 (Repeat 2) 1.63 620 1480 Example 1 (repeat 3) 1.64 610 1490 Example 1 (average value) 1.64 610 1490 Example 2 (repeat 1) 1.75 500 1600 Example 2 (Repeat 2) 1.73 510 1580 Example 2 (repeat 3) 1.74 505 1590 Example 2 (average value) 1.74 505 1590 Example 3 (repeat 1) 1.85 400 1200 Example 3 (repeat 2) 1.83 410 1180 Example 3 (repeat 3) 1.84 405 1190 Example 3 (average value) 1.84 405 1190

[0141] Table 3: Catalyst carbon deposition and deactivation data

[0142]

[0143]

[0144] 6. Experimental summary:

[0145] This experiment conducted a systematic performance test on the catalytic cracking catalysts of rare earth metal modified ZMQ-1 molecular sieves prepared based on three different embodiments. The experimental results showed that the catalysts of different embodiments exhibited their own characteristics and differences in the catalytic cracking reaction, providing rich data support for a deep understanding of the impact of catalyst preparation process on performance.

[0146] Product yield: Light hydrocarbon yield: The catalyst of Example 3 performed well in ethylene and propylene yields, with average values ​​of 23.2% and 16.6% respectively, significantly higher than those of Examples 1 and 2. This is due to the use of mixed rare earth metals (La and Ce) and the finely optimized preparation process, which makes the catalyst have stronger acidity and unique pore structure, which can effectively promote the cracking of heavy hydrocarbon molecules, thereby improving the generation selectivity of light hydrocarbons.

[0147] Distillate oil yield: Example 2 performs better in terms of diesel fraction yield, with an average value of 29.8%, which may be related to the specific metal loading conditions and the structure of the double-layer mesoporous composite oxide in this example, which is conducive to the generation and stability of diesel fraction hydrocarbon molecules. The gasoline fraction yield of Example 1 is relatively stable, with an average value of 33.2%, but compared with other examples, it lacks a clear advantage in the specific distillate oil yield, reflecting that the comprehensive effect of its catalyst composition and process is relatively balanced but not prominent enough.

[0148] Product quality: hydrogen-carbon ratio and heteroatom removal: From the hydrogen-carbon ratio data, the average value of Example 3 is 1.84, which is higher than Example 1 (1.64) and Example 2 (1.74), indicating that the hydrogen content in the generated product is relatively high and the hydrocarbon saturation is good. In terms of nitrogen content and sulfur content, Example 3 also performs well, with an average nitrogen content of 405ppm and an average sulfur content of 1190ppm, which are much lower than other examples. This is because the catalyst formula and preparation process of Example 3 optimize the synergistic effect of metal active centers and acidic centers, enhance the adsorption and conversion capacity of heteroatoms such as nitrogen and sulfur in the raw materials, thereby effectively improving the quality of the product.

[0149] Catalyst stability: carbon deposition and deactivation rate: The average carbon deposition amount of the catalyst in Example 3 is only 12.2%, the ratio of carbon deposition types is 2:3 (soft / hard), and the deactivation rate is the lowest, with an average value of 2.05% / h. This shows that the catalyst has good anti-carbon deposition performance, which may be due to the special structure of the double-layer mesoporous composite oxide and the reasonable combination of rare earth metals and synergistic metals, which reduce the formation of carbon deposition precursors and inhibit the deposition of carbon deposition on the catalyst surface and the conversion into hard carbon deposition that is difficult to remove. In contrast, the carbon deposition amount of Example 1 is higher (average value 18.2%) and the deactivation rate is also faster (average value 3.05% / h), indicating that its stability during long-term reaction is relatively poor.

[0150] Comparative experiment:

[0151] 1. Purpose of the experiment

[0152] By comparing the performance differences of the catalytic cracking catalyst of the rare earth metal modified ZMQ-1 molecular sieve of the present invention (the catalyst prepared in Examples 1, 2 and 3) with the typical catalyst of the traditional prior art in the catalytic cracking reaction, the effectiveness and innovation of the process of the present invention are verified from multiple aspects such as activity, selectivity, stability and resistance to metal poisoning, providing a strong basis for its advantages in industrial applications.

[0153] 2. Experimental Materials and Instruments

[0154] Experimental Materials:

[0155] Catalyst samples prepared in Examples 1, 2 and 3.

[0156] Typical catalyst samples of conventional prior art (select a conventional catalytic cracking catalyst that is widely used in industry and is representative, such as a USY molecular sieve-based catalyst).

[0157] Simulated heavy oil feedstock (containing a variety of hydrocarbons, sulfur-containing and nitrogen-containing compounds and a certain amount of metal impurities, such as nickel, vanadium, etc., whose composition and properties are similar to actual heavy oil).

[0158] High-purity nitrogen (purity ≥ 99.999%) and hydrogen (purity ≥ 99.99%) are used as purge gas, carrier gas and reducing gas of the reaction system.

[0159] Experimental instruments: Continuous flow fixed bed reactor (including reactor, heating furnace, feed pump, back pressure valve and other components, the reactor is made of stainless steel, with an inner diameter of 10 mm and a length of 500 mm). Gas chromatograph (Agilent7890A, equipped with hydrogen flame ionization detector FID and thermal conductivity detector TCD). Elemental analyzer (such as VarioELI II). Inductively coupled plasma emission spectrometer (ICP-AES), used to determine the change in the content of metal impurities on the catalyst before and after the reaction. Thermogravimetric analyzer (TAQ500). Electronic balance (accuracy 0.0001g).

[0160] 3. Experimental steps

[0161] Accurately weigh a certain amount (e.g., 5g) of the catalyst prepared by the first, second, and third embodiments and the traditional prior art catalyst, carefully load into four identical fixed bed reactor constant temperature sections in the glove box, the filling height is 300mm, adopt the segmented filling method and slightly vibrate the reactor to make the catalyst bed uniform and tight, and fill the upper and lower ends with 50mm high inert quartz sand respectively. After filling, the mass of the catalyst loaded is accurately weighed and recorded using an electronic balance. Connect the components of the four reaction devices and check the air tightness of each connecting pipeline. Use nitrogen to purge the entire reaction system, first purge for 1 hour at a flow rate of 100mL / min, exclude the air and impurities in the system, then reduce the nitrogen flow rate to 20mL / min, maintain the system positive pressure, and turn on the heating furnace at the same time, and preheat the four reactors to the reaction temperature (450°C for the primary reactor and 600°C for the secondary reactor). Turn on the feed pump, rinse and calibrate the feed pipeline with a solvent (such as n-heptane) to ensure the accuracy of the feed amount. The back pressure valve pressure was set to 0.1 MPa (first reactor outlet) and 0.2 MPa (second reactor outlet).

[0162] Catalyst pre-reduction (if necessary): For catalysts containing reducible metals and requiring pre-reduction (such as the catalyst treated in a hydrogen / N2 reducing atmosphere in Example 1), a pre-reduction operation is required before the reaction. Raise the temperature of the corresponding reactor to the reduction temperature (such as 400°C), switch the gas to a hydrogen / nitrogen mixed gas (the volume ratio is set according to the catalyst requirements, such as 1:9), and pass it through the catalyst bed at a flow rate of 50mL / min for 4 hours. After the reduction is completed, switch back to nitrogen purging, and start feeding the raw materials after the temperature drops to the reaction temperature. Traditional prior art catalysts are operated according to their standard pretreatment methods.

[0163] Reaction process: After the simulated heavy oil feedstock is preheated to 300°C, it is transported to the top of four primary reactors by a feed pump at a set flow rate (the feed rate of the primary reactor is 10mL / h, and the feed rate of the secondary reactor is calculated according to the catalyst / feedstock ratio) for reaction. After the reaction product flows out from the bottom of the primary reactor, it is heated to the inlet temperature of the secondary reactor through a heating pipeline and then enters the secondary reactor to continue the reaction.

[0164] During the reaction, liquid products and gaseous products were collected from the gas-liquid separators at the outlets of the four reactors every hour. The liquid products were collected in pre-weighed sample bottles, and the gaseous products were switched to the gas chromatograph through a six-way valve for online analysis at an interval of 30 minutes. The reaction lasted for 20 hours to more comprehensively investigate the stability of the catalyst.

[0165] Product analysis: Gas product analysis: Use gas chromatograph (FID to detect hydrocarbons, TCD to detect hydrogen, nitrogen and other permanent gases) to analyze the content of each component in the gas product (including light hydrocarbons such as ethylene, propylene, methane, ethane, propane, as well as hydrogen, nitrogen, carbon monoxide, carbon dioxide, etc.), use standard gas mixture to calibrate the chromatographic column and establish the quantitative analysis method, and use the external standard method to calculate the volume fraction of each component.

[0166] Liquid product analysis: Weigh the collected liquid product and calculate the yield of the liquid product. Then use a distillation device to separate the liquid product into a gasoline fraction (initial boiling point -200°C), a diesel fraction (200°C-350°C) and a heavy fraction (>350°C), record the volume and mass of each fraction, and calculate its yield.

[0167] A certain amount of gasoline fraction and diesel fraction was taken and a detailed hydrocarbon composition analysis was performed using a gas chromatography-mass spectrometer (GC-MS) to determine the distribution of various hydrocarbons such as alkanes, cycloalkanes, and aromatics.

[0168] An elemental analyzer is used to determine the contents of carbon, hydrogen, nitrogen and sulfur in the liquid product, and parameters such as the hydrogen-to-carbon ratio, nitrogen content and sulfur content are calculated to evaluate the catalyst's ability to remove heteroatoms in the raw material.

[0169] Analysis of catalyst carbon deposition and metal poisoning: After the reaction, the catalysts in the four reactors were cooled to room temperature under nitrogen protection, and some catalyst samples (about 100 mg) were taken out respectively for carbon deposition analysis using a thermogravimetric analyzer. The samples were heated from room temperature to 800°C at a heating rate of 10°C / min, and the weight loss of the catalyst was measured under a nitrogen atmosphere. The amount of carbon deposition on the catalyst was calculated based on the weight loss curve, and the type of carbon deposition (such as soft carbon deposition and hard carbon deposition) was determined by analyzing the characteristic peaks of thermal decomposition of carbon deposition.

[0170] In addition, catalyst samples were taken before and after the reaction, and the changes in the content of metal impurities (nickel, vanadium, etc.) on the catalyst were measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES) to evaluate the catalyst's ability to resist metal poisoning.

[0171] IV. Experimental Design

[0172] A completely randomized experimental design was adopted, with the three catalysts of the present invention and the conventional catalyst of the prior art as four treatment groups, and each treatment group was subjected to three repeated experiments. The experiments were conducted under the same reaction conditions, raw material properties and analytical methods to eliminate the influence of systematic errors on the experimental results and ensure the reliability and comparability of the experimental data.

[0173] 5. Experimental results data table

[0174] Table 1: Product yield data

[0175]

[0176]

[0177] Table 2: Product quality data

[0178]

[0179]

[0180] Table 3: Catalyst carbon deposition and metal poisoning data

[0181]

[0182]

[0183] 6. Experimental Summary

[0184] This comparative experiment comprehensively evaluated the performance of the catalytic cracking catalyst of the rare earth metal modified ZMQ-1 molecular sieve of the present invention and the traditional prior art catalyst in the catalytic cracking reaction. The results clearly demonstrated the significant advantages and innovation of the catalyst of the present invention.

[0185] Product yield: The three examples of the catalysts of the present invention have higher ethylene and propylene yields than the conventional catalysts. The performance of Example 3 is particularly outstanding, with an average ethylene yield of 23.2% and an average propylene yield of 16.6%, which are 54.7% and 66.0% higher than the conventional catalysts, respectively. This shows that the special composition and structure of the catalyst of the present invention can more effectively convert heavy oil into high value-added light hydrocarbon products, and has great potential in improving the economic benefits of petrochemical products.

[0186] In terms of distillate oil yield, Example 2 has certain advantages in diesel fraction yield, with an average value of 29.8%, while the average diesel fraction yield of the conventional catalyst is 24.8%. The gasoline fraction yield of Examples 1 and 3 is not much different from that of the conventional catalyst, but from the perspective of the comprehensive light hydrocarbon yield, the catalyst of the present invention is more flexible and efficient in regulating product distribution, and can be optimized in a targeted manner according to market demand.

[0187] Product quality: From the data of hydrogen-carbon ratio and heteroatom content, it can be seen that the catalyst of the present invention is significantly better than the traditional catalyst. The average hydrogen-carbon ratio of Example 3 is 1.84, while the traditional catalyst is only 1.50, which means that the product hydrocarbons generated by the catalyst of the present invention have higher saturation and better quality. In terms of nitrogen content and sulfur content, the average nitrogen content of Example 3 is 405ppm, and the average sulfur content is 1190ppm, which are 50.0% and 40.2% lower than the traditional catalyst, respectively, indicating that the catalyst of the present invention has excellent performance in reducing the content of harmful impurities in the product, which helps to produce cleaner fuel oil products and meet increasingly stringent environmental protection requirements.

[0188] Catalyst stability: In terms of carbon deposits and deactivation rate, the catalyst of the present invention exhibits good anti-carbon deposition performance and stability. The average carbon deposit amount of Example 3 is only 12.2%, and the deactivation rate is 2.05% / h, while the average carbon deposit amount of the traditional catalyst is as high as 24.8%, and the deactivation rate is 4.05% / h. This shows that the double-layer mesoporous composite oxide structure of the catalyst of the present invention, the modification of rare earth metals and synergistic metals, and the unique preparation process effectively inhibit the formation of carbon deposits and the deactivation of the catalyst, extend the service life of the catalyst, and reduce the catalyst replacement cost and downtime in industrial production.

[0189] In terms of resistance to metal poisoning, the catalyst of the present invention also performs well. Taking the increase in nickel and vanadium deposition as an example, the average increase in nickel deposition in Example 3 is 3.1%, and the average increase in vanadium deposition is 5.1%, while the average increase in nickel deposition of the traditional catalyst is 10.1%, and the average increase in vanadium deposition is 15.1%. The catalyst of the present invention has better tolerance to metal impurities in the raw materials, reduces the damage of metal impurities to the active center of the catalyst, and further ensures the stability and catalytic performance of the catalyst during long-term operation.

[0190] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve, characterized in that: By weight percentage, it includes the following components: Rare earth metal modified ZMQ-1 molecular sieve 30%-50%, wherein the total content of rare earth metal and synergistic metal is 5%-15% of the molecular sieve weight; Double-layer mesoporous composite oxide 20%-40%; Binder 15%-25%; Enhancer 5%-10%.

2. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The rare earth metal is selected from Ce or La, and the synergistic metal is selected from Ni and Pt.

3. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The loading distribution uniformity of the rare earth metal and the synergistic metal on the molecular sieve in the rare earth metal modified ZMQ-1 molecular sieve is not less than 80%.

4. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The double-layer mesoporous composite oxide includes an inner layer of CeO2-La2O3 and an outer layer of TiO2-SiO2.

5. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The specific surface area of ​​the double-layer mesoporous composite oxide is 200-500m 2 / g, pore volume is 0.3-0.8cm 3 / g.

6. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The binder comprises gamma alumina and kaolin in a mass ratio of 1:1, and the reinforcing agent is nano silicon dioxide.

7. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The rare earth metal modified ZMQ-1 molecular sieve is prepared by the following steps: S1.1, calcining ZMQ-1 molecular sieve at a temperature of 550°C-600°C for 4-6h; S1.2, impregnate the calcined molecular sieve with a rare earth metal salt solution with a concentration of 0.1 mol / L, a solid-liquid ratio of 1:10, and an impregnation time of 2-6 h; S1.3, drying the impregnated molecular sieve at a temperature of 80°C-120°C for 10-12h; S1.4, repeat the above impregnation and drying steps, using a synergistic metal salt solution with a concentration of 0.05 mol / L; S1.5, calcining the molecular sieve at a temperature of 550°C to 600°C for 4-6 hours; S1.

6. Carry out reduction treatment in a hydrogen or nitrogen reducing atmosphere at 400°C-450°C for 3-5 hours.

8. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The double-layer mesoporous composite oxide is prepared by the following steps: S2.1, prepare the inner layer CeO2-La2O3, mix Ce(NO3)3·6H2O and La(NO3)3·6H2O in a molar ratio of 1:1, dissolve in deionized water, add ammonia water to adjust the pH to 9, wash and dry the precipitate after reaction at a temperature of 100℃-150℃ for 10-12h; S2.2, followed by calcination at a temperature of 500°C-700°C for 3-6h; S2.3, suspend the inner layer particles in TiO2-SiO2 sol, stir to coat, dry and then calcine at a temperature of 450℃-600℃ for 4-8h to form an outer layer.

9. The catalytic cracking catalyst of a rare earth metal modified ZMQ-1 molecular sieve according to claim 8, characterized in that: The Ti or Si molar ratio of the TiO2-SiO2 sol is 2:1 to 5:

1.

10. The catalytic cracking catalyst of the rare earth metal modified ZMQ-1 molecular sieve according to claim 1, characterized in that: The catalyst is formed by the following process: The rare earth metal modified ZMQ-1 molecular sieve, the double-layer mesoporous composite oxide, the binder and the reinforcing agent are mixed in a ratio of 4:2:2:1 respectively according to weight percentage; Add deionized water, control the moisture content to 20%-25%, stir evenly for 1-3 hours; Pellets with a diameter of 2-4 mm are prepared by extrusion molding equipment; The particles are calcined in an air atmosphere at a temperature of 550°C-600°C for 4-6 hours; and a secondary calcination is performed in an inert atmosphere at a temperature of 750°C-800°C for 6-8 hours.